CuII(atsm) inhibits ferroptosis: Implications for treatment of neurodegenerative disease. (14th January 2020) - Southon, Adam; Szostak, Kathryn; Acevedo, Karla M.; Dent, Krista A.; Volitakis, Irene; Belaidi, Abdel A.; Barnham, Kevin J.; Crouch, Peter J.; Ayton, Scott; Donnelly, Paul S.; Bush, Ashley I.
Abstract : Background and Purpose: Diacetyl‐bis(4‐methyl‐3‐thiosemicarbazonato)copper II (Cu II (atsm)) ameliorates neurodegeneration and delays disease progression in mouse models of amyotrophic lateral sclerosis (ALS) and Parkinson's disease (PD), yet the mechanism of action remains uncertain. Promising results were recently reported for separate Phase 1 studies in ALS patients and PD patients. Affected tissue in these disorders shares features of elevated Fe, low glutathione and increased lipid peroxidation consistent with ferroptosis, a novel form of regulated cell death. We therefore evaluated the ability of Cu II (atsm) to inhibit ferroptosis. Experimental Approach: Ferroptosis was induced in neuronal cell models by inhibition of glutathione peroxidase‐4 activity with RSL3 or by blocking cystine uptake with erastin. Cell viability and lipid peroxidation were assessed and the efficacy of Cu II (atsm) was compared to the known antiferroptotic compound liproxstatin‐1. Key Results: Cu II (atsm) protected against lipid peroxidation and ferroptotic lethality in primary and immortalised neuronal cell models (EC50 : ≈130 nM, within an order of magnitude of liproxstatin‐1). Ni II (atsm) also prevented ferroptosis with similar potency, whereas ionic Cu II did not. In cell‐free systems, Cu II (atsm) and Ni II (atsm) inhibited Fe II ‐induced lipid peroxidation, consistent with these compounds quenching lipid radicals. Conclusions and Implications: The antiferroptotic activity of Cu II (atsm) could therefore be the disease‐modifying mechanism being tested in ALS and PD trials. With potency in vitro approaching that of liproxstatin‐1, Cu II (atsm) possesses favourable properties such as oral bioavailability and entry into the brain that make it an attractive investigational product for clinical trials of ferroptosis‐related diseases.